An analysis about knowledge, attitudes, beliefs and practices of HIV and AIDS among the Himba people of the Kunene region, Namibia - Nakakuwa, Filippine Nekulu; Mitonga, Kabwebwe Honore; De Villiers, Josephine; Iipinge, Scholastika (International Journal of Medicine, 2017)
Objectives: To evaluate the knowledge, attitudes, beliefs, practices and risk perceptions with regard to HIV/AIDS among the Himba people from the Kunene region; and to identify its determinant factors.Design: The research study was quantitative. That is, cross sectional, descriptive and analytical. A total of 290 respondents were posed a number of multiple-choice questions about specific areas: HIV modes of transmission, knowledge on prevention measures, wrong conceptions of HIV/AIDS, beliefs, attitudes and practices.Results: In this study, the mean overall score of knowledge of HIV/AIDS and its transmission modes was found to be 15.8 out of 30 with a 95% confidence interval of [15.1]; [16.5]. It was found that the Himba people’s knowledge on HIV/AIDS does not differ according to the gender of the respondent. In fact, the mean score of knowledge of HIV/AIDS and its modes of transmission among females was 15.9 with a confidence interval of [15.1]; [16.8], whilst the mean score of knowledge of HIV/AIDS and its modes of transmission among males was 15.7 with a confidence interval of [14.5]; [16.8]. Using a bivariate analysis, factors such as condom use as a safer sex practice, level of education, type of marriage, and the gender of the respondents showed a statistically significant association with HIV knowledge at a 0.05 level of significance.Conclusion: There is a need to increase knowledge that can be translated into change in behaviour and practices among the Himba, the efforts of all stakeholders are required. Such efforts include promoting education through mobile schools, intensifying sex education within the community through outreach programmes and putting in place policies integrated with indigenous cultural practices that will lead to positive attitudes and beliefs.